A fluorometric sandwich biosensor based on rationally imprinted magnetic particles and aptamer modified carbon dots for the detection of tropomyosin in seafood products. (February 2022) - Wang, Yanbo; Li, Linfang; Li, Huan; Peng, Yafei; Fu, Linglin
Abstract: Tropomyosin (TM), a major allergen in shellfish, has raised increasing concern in industrialized countries and resulted in an urgent need for accurate, simple, and sensitive methods for tracing its presence in food products. Herein, we proposed a sandwich biosensor that employed the rationally imprinted magnetic particles and aptamer modified carbon dots for the detection of TM in seafood products. The multi-point initiated polydopamine was employed as molecular imprinting polymer on magnetic particles, which was subjected to antifouling surface modification to achieve efficient separation of TM. By taking the aptamer modified carbon dots as signal probes, a sandwich assay was achieved with the limit of detection (LOD) being 30.76 ng mL −1 (S/N = 3). The proposed method not only possessed excellent specificity towards TM but exhibited great accuracy. The sandwich biosensor was further used to quantitatively analyze TM in five shrimp and five shrimp processed products, which proved that the proposed biosensor could detect TM in commercial samples and had a great application prospect. Highlights: Molecular imprinted magnetic particle was developed for tropomyosin separation. Aptamer modified carbon dot was employed as a signal probe. The fluorometric sandwich biosensor exhibited promising performance in real samples.